Analisis Pengambilan Keputusan Manajerial dalam Meningkatkan Kualitas Produk - Novita Surya Aulia Nisa (Yayasan Al Ma'arif Dawuhan, 2025)
This study aims to analyze managerial decision-making in improving product quality in the krupuk kulit rambak (buffalo skin crackers) industry in Kendal. The research focuses on four key indicators: objectives, identification of alternatives, unforeseen factors, and the need for tools to measure achieved outcomes. This study employs a qualitative descriptive research design, conducted at a buffalo skin cracker industry in Kendal. The study involves five informants, comprising one primary informant (manager), two key informants (employees), and two additional informants (consumers). Data collection methods include in-depth interviews and observations, ensuring a comprehensive understanding of the managerial decision-making process. The findings reveal that the managerial decision-making process prioritizes stocking buffalo skin as the primary alternative to enhance product quality. This approach addresses the critical issue of raw material availability, which significantly impacts product performance and quality. By increasing the stock of buffalo skin, the company seeks to optimize production efficiency and maintain consistent quality standards. Furthermore, the decision-making process considers external factors, such as fluctuating raw material supply and consumer demand, as part of the strategic planning framework. This study contributes to the understanding of managerial decision-making in small-scale industries, emphasizing the importance of raw material management in improving product quality. The findings suggest that effective managerial decisions are essential for enhancing competitiveness and ensuring the sustainability of traditional food industries. The research highlights the need for structured decision-making frameworks that consider both internal and external factors in quality improvement strategies.